Residual stress and microstructural features of friction-stir-welded GL E36 shipbuilding steel. Issue 1 (2nd January 2018) - Lemos, G. V. B.; Cunha, P. H. C. P.; Nunes, R. M.; Bergmann, L.; dos Santos, J. F.; Clarke, T.
ABSTRACT: The purpose of the present study was to fulfil the knowledge gap concerning residual stresses evaluation of friction stir welded GL E36 shipbuilding steel. Plates of 6 mm thickness were welded using two different welding speeds (1 and 3 mm s −1 ) at a constant rotational speed of 500 rev min −1 . This led to different thermal cycles and the objective is to analyse the resulting microstructures and residual stress states. Therefore, in this work, residual stresses were evaluated by X-ray diffraction; metallography and microhardness testing were performed to support these measurements. Results showed that welds produced with different heat inputs have distinguishable residual stress distributions. Increases in the welding speed led to higher residual stress and microhardness in the stir zone.